2004
DOI: 10.1002/jmv.20090
|View full text |Cite
|
Sign up to set email alerts
|

Age related differences in humoral immune response to respiratory syncytial virus infection in adults

Abstract: The humoral immune response to Respiratory Syncytial Virus (RSV) was investigated in old and young adults. RSV was identified by culture and/or reverse transcription polymerase chain reaction (RT-PCR) in 52 elderly (mean age 74 years) and 15 young adults (mean age 33 years) with respiratory illness. Preinfection serum neutralizing and binding antibody levels were similar in the two age groups, although older persons had significantly greater serum neutralizing responses to group A RSV (log(2) 2.8 increase vs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 26 publications
4
41
0
2
Order By: Relevance
“…Due to multiple exposures to RSV, normal adult human plasma contains RSV-specific antibodies (2,33). Human IgG in each of 42 adult plasma samples bound efficiently to VLP-19 and also to sF protein (Table 2 and Figure 3D).…”
Section: Resultsmentioning
confidence: 99%
“…Due to multiple exposures to RSV, normal adult human plasma contains RSV-specific antibodies (2,33). Human IgG in each of 42 adult plasma samples bound efficiently to VLP-19 and also to sF protein (Table 2 and Figure 3D).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the results also showed the influence of age on these vitamin D-related immune markers in CAP children aged less than 5 y old. Many previous studies have reported that age is always associated with the immune status of patients with infectious diseases (36,37). CAP, as a respiratory infection disease, also showed an age-related association for its etiology and symptoms (38).…”
Section: Discussionmentioning
confidence: 97%
“…Because all adults have measurable antibody to RSV and responses to vaccination have correlated directly with prevaccination titers in prior RSV vaccine studies, we chose to evaluate this vaccine in terms of the percentage of subjects who achieved high levels of NA that might be expected to be relatively protective [21,[27][28][29]. On the basis of studies of natural infection, and assuming a threshold exists that serum antibody levels are unlikely to exceed, we chose the 67th percentile of baseline titers in an elderly population as a target to judge immunogenicity [30,31]. After vaccination with either RSV vaccine formulation, nearly 80% of vaccinees developed titers that exceeded this target level of antibody.…”
Section: Discussionmentioning
confidence: 99%